STEILNESET MEMORIAL | Peter Zumthor’s Atmospheres as an Architectural Means for Memory - Joy, Kathryn (UST Research Online, 2017)
Steilneset Memorial (2011) in Finnmark County, Norway, was built to honor thememory of those who lost their lives as a result of the seventeenth-century Vardø witch trials. The memorial, consisting of two architectural structures and an art installation set along the rocky coast line, is the product of a collaboration among Swiss architect Peter Zumthor, French artist Louise Bourgeois, and Scandinavian historian Liv Helene Willumsen. Through the completion of Steilneset Memorial’s art and architecture, the history and memory of the witch trials is given an identity. I am interested in how architecture and the philosophy of an architect connect to create places of memory. My intention is to analyze Memory Hall and the Glass Pavilion at Steilneset Memorial through Zumthor's architectural principles as outlined in his text, Atmospheres (2006). Through this examination, I position Zumthor's principles as architectural guiding forces for the design and construction of memorial space. I assert that Zumthor's architecture and atmospheric principles facilitate the construction of memory; the result is atmospheric memory.